Aberturas endodônticas e materiais para cad/cam: efeitos na mecânica de fratura de coroas monolíticas - Andrade, Kallyane G. Navarrete de (2021)
This study evaluated the influence of the conventional and minimally invasive endodontic access approach on the fracture mechanics of three materials, with different elastic modulus (E), used to mill CAD/CAM monolithic crowns: Empress CAD (E = 62 GPa), Suprinity (E = 70 GPa) and Enamic (E = 30 GPa). Forty-five crowns with 1 mm thickness were machined and cemented on composite resin dies (E = 18 GPa). The specimens were then subdivided into three groups according to endodontic access: Control (no access), Conventional Access (3 x 3 x 3 mm triangular shape) and Minimally Invasive Access (1.4 mm circular shape). All accesses were repaired with composite resin and the crowns the subjected to load-bearing test. Enamic was able to bear more load than the other materials (p <0.002), while Empress and Suprinity were similar (p> 0.121). The presence of the access reduced the load-bearing for Empress and Enamic (p <0.002). There were no statistically significant differences between the types of endo access (p> 0.216), regardless of the material. At the time of endodontic access, three Empress and one Suprinity crowns fractured in the Conventional access group and none in the Minimally Invasive access group. In the clinical situation of need for endodontic access to a tooth with a monolithic crown, the material that offers greater predictability is Enamic and the type of endodontic access is the Minimally Invasive, as it reduces the risk of fracture at the opening.